2018
DOI: 10.3126/jucms.v5i1.19048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Surgery on Outcome In Perforation Peritonitis

Abstract: BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A patient with pre-renal acute kidney injury and an altered level of consciousness from shock may have these parameters corrected with adequate resuscitation before surgery and is expected to have a better postoperative outcome than those patients proceeding to surgery with markedly deranged APS. Literature has shown that delayed presentation is a risk factor for poorer outcomes, independent of APACHE II points at admission [ 29 , 30 ]. Therefore, a one-time APACHE II score at admission may not completely predict the likely outcome of care in all patients, particularly when there are delays before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A patient with pre-renal acute kidney injury and an altered level of consciousness from shock may have these parameters corrected with adequate resuscitation before surgery and is expected to have a better postoperative outcome than those patients proceeding to surgery with markedly deranged APS. Literature has shown that delayed presentation is a risk factor for poorer outcomes, independent of APACHE II points at admission [ 29 , 30 ]. Therefore, a one-time APACHE II score at admission may not completely predict the likely outcome of care in all patients, particularly when there are delays before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these causes are due to unsanitary conditions and the use of contaminated water. The adaptation of a healthy lifestyle accompanied by early diagnosis and aggressive resuscitation, in addition to prompt surgical intervention can help avoid complications of acute peritonitis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ruptured appendix is third common cause in this study (17.59%) in another study by Batra P 2013 12 it was 3.82% and 24% in India by Sarkar S 2018 7 . Early surgical intervention with 6 hours along with broad spectrum antibiotics proceeded by aggressive resuscitation improved outcome of peritonitis 13 . Our low mortality was also due to same reasons.…”
Section: Discussionmentioning
confidence: 99%